Identities and bodies in school spaces. The case of female trans students - Cazares López, Jorge Octavio; Ibarra Uribe, Luz Marina; Rodríguez Abad, Angélica (Emerging Trends in Education, 2023)
This article addresses the processes of socialization, transitions and resilience strategies of two college trans women in the state of Morelos. Results of a qualitative research are presented, which, from the life history method, narrates the traditional sociocultural construction of binary gender identities. In particular, it is in school spaces where bodies that do not conform to the norm, such as trans identity, are watched over, repressed and reified. Trans women show their journeys in a context of violence, discrimination and exclusion in the face of non-acceptance of body and identity differences. Resilience strategies made possible the challenge, questioning and transgression of binary and hegemonic identities, in order to move towards the recognition, adaptability and empowerment of female trans students.Key Words. dissident masculinities; transsexuality; socialization; school space; transitions.